Sporothrix schenckii sensu stricto and Sporothrix brasiliensis Are Differentially Recognized by Human Peripheral Blood Mononuclear Cells - Martínez-Álvarez, José A.; Pérez-García, Luis A.; Mellado-Mojica, Erika; López, Mercedes G.; Martínez-Duncker, Iván; Lópes-Bezerra, Leila M.; Mora-Montes, Héctor M. (Frontiers in Microbiology, 2017)
Sporothrix schenckii sensu stricto and S. brasiliensis are usually associated to sporotrichosis, a subcutaneous mycosis worldwide distributed. Comparative analyses between these two species indicate they contain genetic and physiological differences that are likely to impact the interaction with host cells. Here, we study the composition of the cell wall from conidia, yeast-like cells and germlings of both species and found they contained the same sugar composition. The carbohydrate proportion in the S. schenckii sensu stricto wall was similar across the three cell morphologies, with exception in the chitin content, which was significantly different in the three morphologies. The cell wall from germlings showed lower rhamnose content and higher glucose levels than other cell morphologies. In S. brasiliensis, the wall sugars were constant in the three morphologies, but glucose was lower in yeast-like cells. In S. schenckii sensu stricto cells most of chitin and β1,3-glucan were underneath wall components, but in S. brasiliensis germlings, chitin was exposed at the cell surface and β1,3-glucan was found in the outer part of the conidia wall. We also compared the ability of these cells to stimulate cytokine production by human peripheral blood mononuclear cells. The three S. schenckii sensu stricto morphologies stimulated increased levels of pro-inflammatory cytokines, when compared to S. brasiliensis cells; while the latter, with exception of conidia, stimulated higher IL-10 levels. Dectin-1 was a key receptor for cytokine production during stimulation with the three morphologies of S. schenckii sensu stricto, but dispensable for cytokine production stimulated by S. brasiliensis germlings. TLR2 and TLR4 were also involved in the sensing of Sporothrix cells, with a major role for the former during cytokine stimulation. Mannose receptor had a minor contribution during cytokine stimulation by S. schenckii sensu stricto yeast-like cells and germlings, but S. schenckii sensu stricto conidia and S. brasiliensis yeast-like cells stimulated pro-inflammatory cytokines via this receptor. In conclusion, S. brasiliensis and S. schenckii sensu stricto, have similar wall composition, which undergoes changes depending on the cell morphology. These differences in the cell wall composition, are likely to influence the contribution of immune receptors during cytokine stimulation by human monocytes.